Students’ English Fun Activities (SEFA): A Community Service Collaboration Between the English Department of State Islamic Institute Lhokseumawe and Sekolah Sukma Bangsa Lhokseumawe - Nurul Fadhillah; Zurriyati; Nuraini; Erlidawati; Fadhlur Rahman; Nisrina; Khairun Nasir; Salmina Elvia Amanda; Elsya Alfitri Siregar; Dwisa Tastia Susfi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service partnership is the initiative of the English Department at IAIN Lhokseumawe and SSB (Sekolah Sukma Bangsa). Further, under the supervision and selection of English department lecturers, EDSA (English Department Students Association) provides instructors for SSB activities. This SEFA program is an extracurricular class activity consisting of English language enrichment tutorials and activities for SSB students. This initiative was implemented between 6 June and 28 November 2022. This program's goal is to boost students' oral English potential through constant exposure in small groups. Hence, it is expected that this community service would contribute to the improvement of educational outcomes at both institutions.